DEVELOPMENT OF INNOVATIVE ENTREPRENEURIAL ACTIVITY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the need for a deep understanding of entrepreneurship, primarily the concept of innovative entrepreneurship. The concept of “innovation” is analyzed in the interpretation of foreign scientists, it is also described that the concept of innovative entrepreneurship, the economy as a whole, goes back to the old historical dates, and we can observe how this concept developed over time and expanded the scope of significance and influence.